Examining the Early Impacts of the Leading Educators Fellowship on Student Achievement and Teacher Retention - Mihaly, Kata (RAND Corporation, 2015)
The Leading Educators Fellowship program is dedicated to training promising mid-career educators to lead their colleagues in pursuit of student success. This report presents findings from preliminary analyses of the program's impacts on student achievement and teacher retention in both Louisiana and Missouri in the 2011-2012 through 2013-2014 school years for teachers who are program fellows and for the teachers mentored by fellows.